2020
DOI: 10.1096/fj.202000346rr
|View full text |Cite
|
Sign up to set email alerts
|

Electro‐acupuncture alleviates adolescent cocaine exposure‐enhanced anxiety‐like behaviors in adult mice by attenuating the activities of PV interneurons in PrL

Abstract: We recently found that adolescent cocaine exposure (ACE) resulted in an enhancement of the γ‐aminobutyric acid (GABA) neurotransmitter system in the prelimbic cortex (PrL) of adult mice. Here, we aim to further investigate the role of GABAergic transmission, especially parvalbumin (PV) interneurons within PrL in the development of ACE‐induced anxiety‐like behavior, and to assess whether and how electro‐acupuncture (EA) therapeutically manage the ACE‐induced abnormal behaviors in adulthood. ACE mice exhibited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 49 publications
6
15
0
Order By: Relevance
“…Consistent with our previous finding (18), we found that ACE mice exhibited obvious anxiety-like behaviors in their adulthood, which was efficiently suppressed by electro-acupuncture (EA) at acupoints of Baihui (GV 20 Drug abuse such as cocaine during adolescence, a sensitive period of heightened propensity to substance use in humans, enhance risk of developing psychiatric disorders, which even persist into adulthood (2,10,28). Consistent with human and animal studies on ACE (9,18,29,30), ACE mice exhibited more anxiety in their adulthood here. Moreover, we found that CaMKII CL activity was involved in the process of anxiety in ACE mice.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Consistent with our previous finding (18), we found that ACE mice exhibited obvious anxiety-like behaviors in their adulthood, which was efficiently suppressed by electro-acupuncture (EA) at acupoints of Baihui (GV 20 Drug abuse such as cocaine during adolescence, a sensitive period of heightened propensity to substance use in humans, enhance risk of developing psychiatric disorders, which even persist into adulthood (2,10,28). Consistent with human and animal studies on ACE (9,18,29,30), ACE mice exhibited more anxiety in their adulthood here. Moreover, we found that CaMKII CL activity was involved in the process of anxiety in ACE mice.…”
Section: Discussionsupporting
confidence: 94%
“…The electro-acupuncture (EA), a kind of peripheral acupuncture with electric stimulation, has been shown to improve anxiety without adverse effects (16,17). Previously, we found that EA at acupoints of Baihui (GV 20) and Yintang (GV 29) during withdrawal period effectively reduced anxiety in ACE mice of adulthood (18). The claustrum (CL) is a thin stripped nucleus situated between the insular cortex and striatum, which is composed by 90 percent of CaMKIIpositive glutamatergic neurons (CaMKII CL ) (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from experiments and clinics has confirmed that it has an improved effect on SUDs (49,50). Recent studies have proven that EA could alleviate substance abuse, inducing anxiety-like behaviors, in people and mice (22,51).…”
Section: Research Fields and Frontiersmentioning
confidence: 99%
“…Complementary therapy for SUDs, especially acupuncture, is not widely used, regardless of its efficiency. Moreover, the involvement of adolescents in CAM for SUDs is considered distressing (21)(22)(23).…”
Section: Analysis Of Abstractmentioning
confidence: 99%
“…Interestingly, a large number of studies reported that EA exerts neuroprotective effects by regulating the structure and function of the hippocampus and PFC (He et al, 2018;Chen et al, 2019;Marcus et al, 2020). For example, preclinical studies reported that EA ameliorate learning, memory and emotion regulating ability via regulating the neurochemical metabolism, cannabinoid receptors expression as well as activation of PV interneurons in the hippocampus and PFC (He et al, 2018;Chen et al, 2019;Marcus et al, 2020;Nie et al, 2020), which are regions of central importance in PTSD due to their prominent role in the neuroendocrine stress response and memory Lambert and McLaughlin, 2019;Smith et al, 2019). Clinical and preclinical studies have previously reported that EA is protective against PTSD (Wang et al, 2012;Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%